ELEVATING FISHEaS OF DAL IN J SH - Ojha, S. N.; Biradar, R. S.; Shah, Tasaduq H.; Ali, Shaukath (Journal of Indian Fisheries Association, 2015)
The deteriorating condition of one of the most magnificent lakes of India,the Dal Lake, has provoked a lot of research interest from the biological andecological points of view. However, the impact of deterioration of the ecologyon the inhabitant fisherfolk around Dal Lake has not been given muchimportance. In this study, the three major beats of the lake, namely, Hazratbal,Nishat and Nehru Park, were surveyed, randomly taking 10% of the fishermenfamilies. It was observed that the summer mean catch per day (5.18 t 0.69kg) was more than the mean winter catch per day (2.85 t 0.40 kg). However,the total annual catch per person was only 1195.56 t 211.63 kg. Moreover,marketing through middlemen, especially, during summer, was observed tobe very low fetching in terms of mean price per kilogramme fish, amountingto Rs 37.50 t 2.54 for local fish and Rs 22.50 t 2.88 for the carp. It was alsoobserved that the fisherfolk had borrowed a good amount of money for therepair and construction of their houses and boats. Therefore, on the whole,the fishing business around Dal Lake was observed to be under severe stress.In this context, this paper has come out with recommendations to uplift thesocio-economic conditions of the fishers.Key words: Dal Lake, socio-economics, fisherfolk